2016
DOI: 10.1002/cb.1589
|View full text |Cite
|
Sign up to set email alerts
|

Three peas in the pod of consumer imagination: Purchase task, involvement, and ad information

Abstract: The research investigates the mediating role of the consumer imagination in persuasion, depending upon level of involvement, nature of the purchase task, and ad information. The consumer imagination is conceptualized as combining triggered information from memory with incoming ad information to simulate a yet‐to‐be‐experienced event. The research reveals how obstacles to information flowing from memory or information from incoming peripheral ad claims suppress the enhancing effects of the consumer imagination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…as Li et al (2003) indicate, enjoyment is a critical part of VR strategies to induce telepresence. Additionally, higher cognitive involvement with hedonic products leads to more positive brand evaluations (Spears et al, 2016). Therefore, VR strategies for hedonic products are likely to be more successful in the high involvement path.…”
Section: Choosing a Strategic Level Of Involvement: The Role Of Produmentioning
confidence: 99%
“…as Li et al (2003) indicate, enjoyment is a critical part of VR strategies to induce telepresence. Additionally, higher cognitive involvement with hedonic products leads to more positive brand evaluations (Spears et al, 2016). Therefore, VR strategies for hedonic products are likely to be more successful in the high involvement path.…”
Section: Choosing a Strategic Level Of Involvement: The Role Of Produmentioning
confidence: 99%
“…First and foremost, this research illustrates the underlying impact of autobiographical memory on brand retrieval and purchase intentions from a cognitive point of view. This adds to the marketing literature that has linked autobiographical memory to advertising effectiveness (e.g., Spears et al, 2016), but primarily from an affective point of view, showing an impact on consumer attitudes (e.g., Praxmarer, 2011) and occasionally purchase intentions (e.g., Wei et al, 2020). In contrast, the present study concentrated on brand retrieval and purchase intention as they are two cognitive aspects known to have a stronger bearing on consumer choice than attitudes.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast to generic or abstract information, autobiographical memories hinge on personal experiences, which are time and context specific (Sujan et al, 1993). Existing research has shown that cueing autobiographical memories can enhance advertising effectiveness (e.g., Braun, 1999; Braun‐LaTour et al, 2004; Spears et al, 2016; Sujan et al, 1993). However, past studies have largely focused on affective implications; that is, the feelings and emotions aroused by a retrieved autobiographical episode, which influence brand meaning and brand attitudes (see Praxmarer, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumer decision-making process refers to a linear model that illustrates the behavioral patterns demonstrated as they occur across various stages of the shopping experience (Karimi, Papamichail, & Holland, 2015). Decision making is defined as the information-intake process through which people integrate as much as information as possible (Neslin et al, 2006; Spears, Ketron, & Ngamsiriudom, 2016). Traditional consumer decision-making process models describe this as a five-stage process, which includes need recognition, information searches, evaluation of alternatives, and purchase and post-purchase phases (Neslin et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%